2019
DOI: 10.1155/2019/7092695
|View full text |Cite
|
Sign up to set email alerts
|

Active Ageing Level and Time Use of Elderly Persons in a Thai Suburban Community

Abstract: Elderly populations are growing rapidly worldwide, thus enhancing an increasing need for their independent health care, productivity, and most importantly, balance of occupations. This research is aimed at investigating the active ageing levels and time use patterns of an elderly population attending the Community Elderly School in a suburban village of northern Thailand. These participants comprised 140 persons aged 60 years and older and were without cognitive deficits, based on the Mini-Mental State Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 21 publications
4
32
0
4
Order By: Relevance
“…The North had the highest percentage of older-person households (of total households), yet also had the lowest prevalence of household need for caregivers of older persons, and the trend was relatively stable. That finding might partly be explained by more engagement in social activities and self-reliance of older people in the North [52]. Indeed, further analyses on the data for this study found that the prevalence of being a member and actively participating in old age citizen’s groups in the North region was higher than all the other regions and across time.…”
Section: Discussionmentioning
confidence: 67%
“…The North had the highest percentage of older-person households (of total households), yet also had the lowest prevalence of household need for caregivers of older persons, and the trend was relatively stable. That finding might partly be explained by more engagement in social activities and self-reliance of older people in the North [52]. Indeed, further analyses on the data for this study found that the prevalence of being a member and actively participating in old age citizen’s groups in the North region was higher than all the other regions and across time.…”
Section: Discussionmentioning
confidence: 67%
“…Such people in rural areas or suburban communities in ailand have less opportunity to use hi-tech devices, including the emergency alert device, and most elderly people perform their daily activities alone. In addition, the percentage of performance in daily activities when alone was highest in the low active aging group [16]. e prototype of this device was designed with a familiar wristwatch appearance, which helped the users feel comfortable and not like a robot with a special device.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of older persons has become a global phenomenon and is becoming a vital topic around the world (Autchariya, Suchitporn & Supawadee, 2019;Hadeel et al, 2018). As highlighted by the United Nations (2015a), the number of older persons was reported to increase substantially in most countries and regions whereby one in eight people worldwide was aged 60 years old or overreached 901 million in the year 2015.…”
Section: Introductionmentioning
confidence: 99%